2011
DOI: 10.1080/00218464.2011.600675
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Predicting the Stresses in Adhesive Joints after Cyclic Moisture Conditioning

Abstract: The durability of adhesive joints is of special concern in structural applications and moisture has been identified as one of the major factors affecting joint durability. This is especially important in applications where joints are exposed to varying environmental conditions throughout their life. This paper presents a methodology to predict the stresses in adhesive joints under cyclic moisture conditioning. The single lap joints were manufactured from aluminium alloy 2024 T3 and the FM73-BR127 adhesive-prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Lin and Chen [55] observed that the reduction in the elastic modulus of epoxy samples for the saturated, dried and re-saturated groups is 29%, 9% and 42% respectively, compared with the unaged group samples. Very similar results were also reported by Mubashar et al [56]. Roy et al [57] found that the 20% drop in the elastic modulus of epoxy adhesive samples aged in water at 40°C would be fully restored upon drying.…”
Section: Effect Of Moisture On Resins and Adhesivessupporting
confidence: 87%
“…Lin and Chen [55] observed that the reduction in the elastic modulus of epoxy samples for the saturated, dried and re-saturated groups is 29%, 9% and 42% respectively, compared with the unaged group samples. Very similar results were also reported by Mubashar et al [56]. Roy et al [57] found that the 20% drop in the elastic modulus of epoxy adhesive samples aged in water at 40°C would be fully restored upon drying.…”
Section: Effect Of Moisture On Resins and Adhesivessupporting
confidence: 87%
“…The drastic reduction of the G IIC values ascertained when comparing the findings for sets of aged and unaged CFRP joints coincides with the fact that the onset of crack propagation was observed at the side of the specimen where the moisture concentration and thermal effect are higher [34]. Additionally, the crack propagation occurred near the adhesive region, and diffusion through the adhesive is regarded as the primary access route for moisture to enter a joint [35].…”
Section: Aging Effectsupporting
confidence: 61%
“…The appearance of microcracks caused by swelling becomes more pronounced when cycles of water absorption and desorption occur, since the microcracks act as routes for the diffusion of water, intensifying the moisture absorption of the material and consequently increasing the degradation. Under cyclic exposure to moisture and drying, the ductility obtained by absorbing water can be lost [4,143]. This is yet another reason for needing to determine the behavior of adhesives and resins based on absorption and desorption history.…”
Section: Moisturementioning
confidence: 99%